Prosthetic Joint Infection: The Challenges of Prevention, Diagnosis and Treatment and Opportunities for Future Research - Benito, Natividad; Murillo, Óscar; Lora-Tamayo, Jaime (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint brings together a group of articles that were published as a Special Issue on prosthetic joint infection in the journal Antibiotics. They cover various aspects of risk factors and prevention, medical and surgical treatment, and outcomes of prosthetic joint infections.